Experiences and Perspectives on Adopting New Practices for Social Needs-targeted Care in Safety-net Settings: A Qualitative Case Series Study. (May 2021) - Nehme, Eileen; Castedo de Martell, Sierra; Matthews, Hannah; Lakey, David
Introduction: Clinical settings are being encouraged to identify and address patients' social needs within the clinic or through partner organizations. The purpose of this qualitative study was to describe the current practice of social needs-targeted care in 3 Texas safety net clinics, and facilitators and barriers to adopting new social needs-targeted care tools and practices. Methods: Interviews were conducted with staff at 3 safety net clinics serving small and mid-sized communities. Analysis focused on perspectives and decisions around adopting new tools or practices related to social needs-targeted care, including standardized screening tools and community resource referral platforms. Results: Nine staff across 3 organizations were interviewed. Two organizations were currently using a standard social needs screening tool in their routine practice, and a third was considering doing so. One organization had adopted a community resource referral platform in partnership with a large community collaboration. Three case studies illustrate a range of facilitators, barriers, perceived benefits, and drawbacks influencing social needs-targeted practices. Benefits of systematic data collection on social needs included the generation of data for community action. Drawbacks include concerns about data privacy. Community resource referral platforms were seen as valuable for creating accountability, but required an influential community partner and adequate community resources. Concerns about disempowering clients and blurring roles were voiced, and potential to increase provider job satisfaction was identified. Conclusions: Benefits and drawbacks of adopting new tools and practices related to social needs-targeted care are strongly influenced by the community context. For the adoption of community resource referral platforms, the outer setting is particularly relevant; adoption readiness is best assessed at the community or regional level rather than the clinic system level. While screening tools are much easier than referral platforms for clinics to adopt, the ability to address identified needs remains heavily based on the outer setting.